Scheduled Deliveries: Avoiding Iatrogenic Prematurity - Chescheir, Nancy; Menard, M. Kathryn (American Journal of Perinatology, 2012)
The balance of maternal, fetal, and neonatal risks of continued pregnancy versus iatrogenic delivery must be based on best evidence. Although avoiding elective deliveries prior to 39 weeks is well established to improve neonatal outcomes, several “soft” conditions are commonly considered to require delivery prior to 39 weeks. Review of existing literature suggests that with some of these conditions, delivery can be safely delayed until later in pregnancy or even allowed to proceed without intervention. Late preterm and early term deliveries contribute substantially to neonatal morbidity and health care costs and should be considered only if the risks of continuing the pregnancy exceed the neonatal risks related to early birth. In this article, we review some the common clinical scenarios that may result in scheduled early term or late preterm births, with a focus on practice strategies for improving maternal and neonatal outcomes.
Keywords: elective delivery; induction of labor; late preterm birth